After market service inventory management - Ang, Zi Qiang (2010)
Inventory rationing is becoming more and more widely applied in many industries. Classic examples include the airline industry and hotel management whereby customers are differentiated in terms of the service required by each customer. Aftermarket service provision is gaining recognition as well as companies realized that a big portion of the total revenue actually comes from here. An example of aftermarket service is the provision of supporting service parts for military weapon systems, a study done by Cohen [1]. Many studies had been done to show the effectiveness of inventory rationing in minimizing cost in providing parts and service for both before and after market. Hence we can see that a good inventory management system is equally important in both before and after market sale of parts and services.